(untitled) (Statistics, Optimization & Information Computing, 2025)
In this paper, two-echelon inventory control system is discussed in supply chain using fuzzy number. The system consists of a manufacturer and single retailer. In our proposed model, manufacturer is an upper and retailer node is lower in echelon system and non-coordination supply chain model is investigated. Different types of demand models are given, particularly quadratic model is discussed. Here triangle fuzzy number is used for fuzzification and Graded Mean Integration and signed distance method are used for defuzzification. Some necessary theorems are proved.